A methodology for e-Readiness Computation using Divide, Predict and Conquer Approach - Sharma, Gajendra; Sharma, Deep Raj (Journal of the Institute of Engineering, 2017)
There exist some problems which seem partially similar to Divide and Conquer approach but can’t be solved using this approach. Such type of problems can be divisible into sub problems of different size but the same mechanism may not be useful to solve all of the sub problems. While using the same mechanism to solve all of the sub problems they can be classified into two kinds, first having a solution, second having no solution. The proposed approach in this paper analyses the features of sub-problems that can be solved and finds a solution for the unsolvable problems using those features. Further, we advocate this method is suitable for computation of e-Readiness in developing countries like Nepal, who are bounded to invest a very low budget in Technological Researches.Journal of the Institute of Engineering, 2016, 12(1): 143-150